The Capital-labor-time Triad as a Key Factor of Economic Knowledge - Dobija, Mieczyslaw; Renkas , Jurij (Recent Progress in Science and Technology Vol. 8, 2023)
In the works of economists, one still encounters the perception of capital as tangible or intangible assets. The understanding of capital stems from the principle of dualism, which is the basis of accounting theory and the measurement of periodic income of economic units. From this principle it follows that capital is an abstract category. In energy-material processes, capital represents the abstract ability to do work. Thus, mathematics providing abstract tools and thermodynamics capable of describing the transformation of energy and work are used to describe capital. Consideration of the principles of thermodynamics is necessary when measuring periodic profits, asset depreciation and equivalent wages. The consistent application of the second principle of thermodynamics leads to the conclusion that the natural constant revealed in the theory of human capital measurement also determines the rate of passage of time so the triad of capital-labor-time is the foundation of economic knowledge. Theoretical analyses and findings are confirmed by empirical studies.